2022
DOI: 10.3390/min12050610
|View full text |Cite
|
Sign up to set email alerts
|

Pb-Bearing Ferrihydrite Bioreduction and Secondary-Mineral Precipitation during Fe Redox Cycling

Abstract: The significant accumulation of Pb from anthropogenic activities threatens environmental ecosystems. In the environment, iron oxides are one of the main carriers of Pb. Thus, the redox cycling of iron oxides, which is due to biotic and abiotic pathways, and which leads to their dissolution or transformation, controls the fate of Pb. However, a knowledge gap exists on the bioreduction in Pb-bearing ferrihydrites, secondary-mineral precipitation, and Pb partitioning during the bioreduction/oxidation/bioreduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…The value obtained for the starch free material (CP-R0) is lower than the theoretical value of the bulk magnetite (92 emu g -1 (Han et al, 1994)). Previous reports on Fe3O4 NP (Amir et al, 2016;Byrne et al, 2013;Daou et al, 2008Daou et al, , 2006Kotsikau et al, 2018;Meite et al, 2022bMeite et al, , 2022aZegeye et al, 2021) indicated that Ms decreases with particle size (see inset of Fig 6). Our results on CP-R0, as well as on OP-R0 (Ms = 89.1 emu g -1 for 67 nm particles), are fully consistent with the reported trend.…”
Section: Magnetization Measurementsmentioning
confidence: 63%
“…The value obtained for the starch free material (CP-R0) is lower than the theoretical value of the bulk magnetite (92 emu g -1 (Han et al, 1994)). Previous reports on Fe3O4 NP (Amir et al, 2016;Byrne et al, 2013;Daou et al, 2008Daou et al, , 2006Kotsikau et al, 2018;Meite et al, 2022bMeite et al, , 2022aZegeye et al, 2021) indicated that Ms decreases with particle size (see inset of Fig 6). Our results on CP-R0, as well as on OP-R0 (Ms = 89.1 emu g -1 for 67 nm particles), are fully consistent with the reported trend.…”
Section: Magnetization Measurementsmentioning
confidence: 63%